Comprehensive Simulation of Ca2+ Transients in the Continuum of Mouse Skeletal Muscle Fiber Types (2021)
ABSTRACT: Mag-Fluo-4 has revealed differences in the kinetics of the Ca2+ transients of mammalian fiber types (I, IIA, IIX, and IIB). We simulated the changes in [Ca2+] through the sarcomere of these four fiber types, considering classical (troponin –Tn–, parvalbumin –Pv–, adenosine triphosphate –ATP–, sarcoplasmic reticulum Ca2+ pump –SERCA–, and dye) and new (mitochondria –MITO–, Na+/Ca2+ exchanger –NCX–, and store-operated calcium entry –SOCE–) Ca2+ binding sites, during single and tetanic stimulation. We found that during a single twitch, the sarcoplasmic peak [Ca2+] for fibers type IIB and IIX was around 16 µM, and for fibers type I and IIA reached 10–13 µM. The release rate in fibers type I, IIA, IIX, and IIB was 64.8, 153.6, 238.8, and 244.5 µM ms−1, respectively. Both the pattern of change and the peak concentrations of the Ca2+-bound species in the sarcoplasm (Tn, PV, ATP, and dye), the sarcolemma (NCX, SOCE), and the SR (SERCA) showed the order IIB ≥ IIX > IIA > I. The capacity of the NCX was 2.5, 1.3, 0.9, and 0.8% of the capacity of SERCA, for fibers type I, IIA, IIX, and IIB, respectively. MITO peak [Ca2+] ranged from 0.93 to 0.23 µM, in fibers type I and IIB, respectively, while intermediate values were obtained in fibers IIA and IIX. The latter numbers doubled during tetanic stimulation. In conclusion, we presented a comprehensive mathematical model of the excitation–contraction coupling that integrated most classical and novel Ca2+ handling mechanisms, overcoming the limitations of the fast- vs. slow-fibers dichotomy and the use of slow dyes.